2021
DOI: 10.3390/cryst11121523
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Study of Internal Heating and Chemical Reaction Effects on MHD Flow of Nanofluid with Convective Conditions

Abstract: This research investigates the influence of the combined effect of the chemically reactive and thermal radiation on electrically conductive stagnation point flow of nanofluid flow in the presence of a stationary magnetic field. Furthermore, the effect of Newtonian heating, thermal dissipation, and activation energy are considered. The boundary layer theory developed the constitutive partial differential momentum, energy, and diffusion balance equations. The fundamental flow model is changed to a system of coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Thus, when the value of p changes continuously from 0 to 1, the homotopy solution also runs from initial guess 𭟋 0 (ξ), Θ 0 (ξ), and Φ 0 (ξ) to the accurate solution, 𭟋(ξ), Θ(ξ), and Φ(ξ) according to Liao [53]. As Haroon Ur Rasheed [54] did, we expand using Taylor series expansion rule about p = 0, and hence we have the following results.…”
Section: 𭟋(ξ;mentioning
confidence: 99%
“…Thus, when the value of p changes continuously from 0 to 1, the homotopy solution also runs from initial guess 𭟋 0 (ξ), Θ 0 (ξ), and Φ 0 (ξ) to the accurate solution, 𭟋(ξ), Θ(ξ), and Φ(ξ) according to Liao [53]. As Haroon Ur Rasheed [54] did, we expand using Taylor series expansion rule about p = 0, and hence we have the following results.…”
Section: 𭟋(ξ;mentioning
confidence: 99%
“…Several researchers have examined the characteristics of fluid flow and heat transmission in numerous technical applications [1][2][3][4]. In the last decade, high-conductivity nanoparticles have been presented as a means of enhancing heat transmission [5][6][7][8]. The dissolving of nanoparticles in the base fluid produces a fluid known as a nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…In this problem, they found that the augmented approximation of the porosity term decreased the nanoliquid Nusselt number. Rasheed et al 44 used the convective conditions and internal heating source for the flow of a nanoliquid. It was seen that the expansion in the magnetic parameter led to improving the thermal profile of the nanoliquid.…”
Section: Introductionmentioning
confidence: 99%